2022
DOI: 10.3389/fenvs.2021.767871
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Evaluation of the Existing Approaches for Controlling and Managing the Proliferation of Water Hyacinth (Eichhornia crassipes): Review

Abstract: The proliferation of the invasive Water hyacinth (WH) plant leads to ecological, economic, public health, and agricultural problems. Several efforts have been deployed to control its spread, but no concreate results have been obtained. Only few studies dealing with systematic approaches for the WH control have been conducted. To establish a road map for the best control methods to be adopted, this review highlights the control programs that have been tested worldwide and describes, through a deep literature an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…Based on the compilation of large-scale experiences of water hyacinth control programmes in 26 countries conducted by Karouach et al (2022), our work can be considered the longest water hyacinth biocontrol programme studied to date. The control of germinated water hyacinth plants in the Dique Los Sauces reservoir is another good example of successful CBC of weeds.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the compilation of large-scale experiences of water hyacinth control programmes in 26 countries conducted by Karouach et al (2022), our work can be considered the longest water hyacinth biocontrol programme studied to date. The control of germinated water hyacinth plants in the Dique Los Sauces reservoir is another good example of successful CBC of weeds.…”
Section: Discussionmentioning
confidence: 99%
“…Physical control remains the only method through which WH can be transformed into value-added products [16]. However, the significant disadvantage of this mechanism is that it expends a great deal of energy and needs a high investment cost [56].…”
Section: Physical Controlmentioning
confidence: 99%
“…Fresh WH cooked with rice grain and fish feast and blended with vegetable waste, rice bran, copra cake, and salt and copra meal is utilized as feed for pigs, ducks, and lake fish in nations like Thailand, Malaysia, China, and the Philippines [57]. Other researchers also showed the utilization of WH as dairy cattle feed [56]. Akinwande et al [68] also, with their study conducted on three water bodies in Nigeria, demonstrated that biomass yield, synthetic arrangement, and nutritive capability of WH to be used as feed for creatures, particularly ruminants.…”
Section: Animal Fodder: Nonconventional Source Of Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…To control WH, several strategies have been employed, including physical control by manual removal and mechanical dredging, chemical control by spraying herbicides, biological control by releasing insect enemies and pathogenic fungi, and integrated control by combining two or more of the above-mentioned methods [ 6 ]. In addition to the drawbacks, including laborious, environmentally unfriendly and unstable in terms of efficiency, the cost for WH management is relatively high [ 4 , 7 , 8 ]. For example, almost $46 million has been spent on managing aquatic invasive weeds, mainly WH, in the California Bay-Delta during 2013–2016 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%